Systemic inflammatory biomarkers as predictive and prognostic factors in men with metastatic castration-refractory prostate cancer treated with docetaxel therapy: a comprehensive analysis in a German real-world cohort - Neuberger, Manuel; Goly, Nora; Skladny, Janina; Milczynski, Veronica; Weiß, Christel; Wessels, Frederik; Nitschke, Katja; Grüne, Britta; Haney, Caelán Max; Hartung, Friedrich; Herrmann, Jonas; Jarczyk, Jonas; et al. (Journal of cancer research and clinical oncology, 2023)
Advances in therapy of metastatic castration-refractory prostate cancer (mCRPC) resulted in more therapeutic options and led to a higher need of predictive/prognostic biomarkers. Systemic inflammatory biomarkers could provide the basis for personalized treatment selection. This study aimed to assess the modified Glasgow Prognostic Score (mGPS), the neutrophile-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR) and the systemic immune-inflammation index (SII) in men with mCRPC under docetaxel.
Online veröffentlicht: 8. August 2022
Gesehen am 09.07.2024